Urgency of Separation of Powers in State Institutions to Defend Against Corruption in Indonesia - Fatria Khairo; Firman Freaddy Busroh; Rianda Riviyusnita (Lex Publica, 2019)
The issue of abuse of authority is still a color of politics in every state institution, such as the ministry. Such as political member charges. There are ways for brainstorming for writers to contribute to the system as we know that Indonesia implements a system of power-sharing known as the Legislative, Executive and Judiciary. With its power distribution system, Indonesia tends to open space for corrupt behavior. The Urgency of the Separation of Power System in corruption in Indonesia aims to reduce the space that can be corrupted and to facilitate monitoring and evaluation of each performance. Abstrak Isu penyalahgunaan wewenang masih menjadi warna politik di setiap lembaga negara, seperti kementerian. Seperti biaya anggota politik. Ada cara untuk brainstorming bagi penulis untuk berkontribusi pada sistem. Seperti kita ketahui bahwa Indonesia menerapkan sistem pembagian kekuasaan yang dikenal dengan Legislatif, Eksekutif dan Yudikatif. Indonesia dengan sistem distribusi kekuasaan cenderung membuka ruang perilaku korupsi. Urgensi Pemisahan Sistem Ketenagalistrikan dalam korupsi di Indonesia ditujukan untuk mengurangi ruang yang berpeluang dikorupsi dan untuk memudahkan monitoring dan evaluasi setiap kinerja. Kata kunci: Korupsi, Pemisahan Sistem Tenaga, Lembaga Negara, Indonesia